HUMIDITY SENSING ELEMENTS BASED ON SILICA-GRAPHENE SURFACE LAYERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents humidity sensing elements based on silica-graphene surface layers, prepared via a sol-gel method. The samples were sintered at temperatures of 400 °C, 600 °C and 800 °C. Tetraethoxysilane was used as a precursor of SiO2 and as a dopant - graphene aggregates of nanoplatelets. A description of the sample preparation procedure is provided. Using a precise impedance analyzer and a calibrator for humidity and temperature, the changes in their resistance R were investigated with variations in relative humidity in the range of 30% to 90% at a temperature of 25 °C and at a frequency of 20 Hz. Morphological observations and map data analyses were carried out by Scanning Electron Microscopy (SEM) and Energy Dispersion Spectroscopy (EDX). The developed sensor elements have a good sensitivity to the humidity, and the resistance change reaches two orders of magnitude. Additions of graphene improve the sensitivity of the elements. The characteristics of the sensing elements at different sintering temperatures and different amounts of graphene dopant were modeled using an artificial neural network.